The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2141.2005.05517.x
|View full text |Cite
|
Sign up to set email alerts
|

An elevated venous haemoglobin concentration cannot be used as a surrogate marker for absolute erythrocytosis: a study of patients with polycythaemia vera and apparent polycythaemia

Abstract: SummaryThe diagnosis of polycythaemia vera (PV) has been established upon sets of clinical criteria, which require the presence of absolute erythrocytosis (AE). The most recent clinical criteria for PV, published by the World Health Organization (WHO) in 2001, also required AE, and stated that the measured red cell mass (RCM) could be replaced by a surrogate marker for AE; a haemoglobin (Hb) value of >18AE5 g/dl in males and >16AE5 g/dl in females. The present study evaluated the potential of venous haematocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 11 publications
4
68
0
2
Order By: Relevance
“…9 It is well known that a proportion of patients suffering from PV do not reach the Hb threshold defined by the WHO. [10][11][12] This is extremely important in those cases with concomitant thrombocytosis. In these cases, if RCM is not measured, the majority of patients may be erroneously classified as ET.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is well known that a proportion of patients suffering from PV do not reach the Hb threshold defined by the WHO. [10][11][12] This is extremely important in those cases with concomitant thrombocytosis. In these cases, if RCM is not measured, the majority of patients may be erroneously classified as ET.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of 77 consecutive patients (31 males and 46 females) with PV in the study of Johansson et al only 35% of male and 63% of female PV patients had Hb values above 18.5 and 16.5 g/dL respectively 21 . Laboratory features at diagnosis of 266 PV and 381 ET patients diagnosed according to Table 7: The Basel data in 13 cases with documented MPN in bone marrow biopsy and 5 case of erythrocytosis: direct comparison and erythrocytes, serum EPO and RCM.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies showed that WHO defined elevated hemoglobin concentration cannot be used as a surrogate marker for absolute erythrocytosis in PV patients indicating the need that RCM is mandatory for patients who do not meet the WHO defined, rather crude hemoglobin and hematocrit value [21][22][23][24]. In a series of 77 consecutive patients (31 males and 46 females) with PV in the study of Johansson et al only 35% of male and 63% of female PV patients had Hb values above 18.5 and 16.5 g/dL respectively 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Four studies showed that WHO defined elevated hemoglobin concentration cannot be used as a surrogate marker for absolute erythrocytosis in PV patients indicating the need by the PVSG and WHO investigators that RCM is mandatory for patients who do not meet the WHO defined crude hemoglobin and hematocrit values [20][21][22][23]. In a series of 77 consecutive patients (31 males and 46 females) with PV in the study of Johansson et al, only 35% of male and 63% of female PV patients had Hb values above 18.5 and 16.5 g/dL respectively [20]. The laboratory features at diagnosis of PVSG defined PV and ET patients from a nation-wide survey of 647 patients with MPN disease in Japan are shown in Table 7 [23].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the relation between RCM, erythrocyte count and bone marrow histology findings at time of diagnosis (Tables 4 and 5) in 12 ET and 14 PV cases with no or minor splenomegaly at time of PV as compared to the 2008 WHO cut-of levels of hemoglobin (Hb) and hematocrit (Ht) for PV: Hb >18.5 g/dl and Ht >0.60 in men and Hb>16.5 and Ht >0.56 in women for the diagnosis of PV (Table 6) [12,[20][21][22][23][24]. At RCM above 30 ml/kg the erythrocytes are above 5.8×10 12 /L in 3 of 10 ET and all 16 PV patients.…”
Section: Rcm and Red Cell Counts On Top Of Bone Marrow Histology Dismentioning
confidence: 99%